Spanish workbook - Stein, Gail (Hoboken, New Jersey : For Dummies, a Wiley Brand, 2023)
Spanish Workbook For Dummies is full of clear explanations and hundreds of practice activities for beginning Spanish learners. You'll learn how to express yourself, ask questions, talk about the past, and construct simple sentences--en español. As you work through the book, complete practice exercises, get lots of writing opportunities, and have tons of fun.
Introduction 1 -- Part 1: Getting Started with the Basics 5 -- Chapter 1: Getting a Jump Start in Spanish 7 -- Chapter 2: Selecting the Proper Part of Speech 33 -- Part 2: The Here and Now 49 -- Chapter 3: Sorting Out Word Gender 51 -- Chapter 4: Coloring Your Sentences with Adjectives 73 -- Chapter 5: Expressing Yourself in the Present 91 -- Chapter 6: Expressing Yourself with Subjunctive Feeling 121 -- Chapter 7: Enriching Your Sentences with Adverbs and Comparisons 149 -- Part 3: Giving and Obtaining Information 163 -- Chapter 8: Getting Answers with the Right Questions 165 -- Chapter 9: Being Clear and Concise with Object Pronouns 185 -- Chapter 10: Reflecting on Reflexive Pronouns and Verbs 205 -- Chapter 11: Getting Attention with Commands 217 -- Chapter 12: Preparing to Connect with Prepositions 239 -- Part 4: Reminiscing about the Past and Seeing into the Future 253 -- Chapter 13: Leaving It Completely in the Past 255 -- Chapter 14: Looking Back with the Imperfect 269 -- Chapter 15: Seeing into the Future 283 -- Part 5: The Part of Tens 293 -- Chapter 16: Ten Most Common Mistakes in Spanish 295 -- Chapter 17: Ten Important Verb Distinctions 301 -- Part 6: Appendixes 307 -- Appendix A: Verb Charts 309 -- Appendix B: Thematic Vocabulary 319 -- Appendix C: English-Spanish Dictionary 331 -- Appendix D: Spanish-English Dictionary 335 -- Index 341.
Includes index.
Keywords: SPANISH LANGUAGE